2009
DOI: 10.1186/1475-2867-9-19
|View full text |Cite
|
Sign up to set email alerts
|

NUCKS overexpression in breast cancer

Abstract: Background: NUCKS (Nuclear, Casein Kinase and Cyclin-dependent Kinase Substrate) is a nuclear, DNA-binding and highly phosphorylated protein. A number of reports show that NUCKS is highly expressed on the level of mRNA in several human cancers, including breast cancer. In this work, NUCKS expression on both RNA and protein levels was studied in breast tissue biopsies consisted of invasive carcinomas, intraductal proliferative lesions, benign epithelial proliferations and fibroadenomas, as well as in primary cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 33 publications
4
32
0
3
Order By: Relevance
“…There are several scientific reports utilizing array-based Comparative Genomic Hybridization (CGH) techniques, which show that there is a high frequency (59-74%) of gain of chromosome region 1q.32 in breast cancer and this gain is an early event in the cancer progression (Nyante et al, 2004). In harmony with our results Drosos et al (2009) reported in his study that the quantitative, real-time RT-PCR analysis of primary culture cells derived from benign lesions and breast carcinomas revealed higher NUCKS-1 gene expression compared to normal and fibroadenoma culture cells.…”
Section: 837 Effect Of Nucks-1 Overexpression On Cytokines Profilingsupporting
confidence: 78%
“…There are several scientific reports utilizing array-based Comparative Genomic Hybridization (CGH) techniques, which show that there is a high frequency (59-74%) of gain of chromosome region 1q.32 in breast cancer and this gain is an early event in the cancer progression (Nyante et al, 2004). In harmony with our results Drosos et al (2009) reported in his study that the quantitative, real-time RT-PCR analysis of primary culture cells derived from benign lesions and breast carcinomas revealed higher NUCKS-1 gene expression compared to normal and fibroadenoma culture cells.…”
Section: 837 Effect Of Nucks-1 Overexpression On Cytokines Profilingsupporting
confidence: 78%
“…Thus, we believe that the expression of NUCKS in different types of skin tumors should be considered as biomarker for tumor malignancy and not for inflammation. This remains in agreement with general findings of the other authors [7] where the most intense NUCKS staining was found in invasive ductal carcinoma compared to normal tissues. In summary, we would like to emphasize that NUCKS is overexpressed in BCC, SCC cells and it is also expressed in KA cells showing much higher expression than that of Ki67.…”
Section: Discussionsupporting
confidence: 83%
“…Some of these analyses related the occurrence of the protein to histological grade or to a particular tumor type and also to benign epithelial proliferations. Several studies performed during the last four years by independent research groups have revealed similar results in relation to significance of NUCKS expression in a number of breast lesions [7,11]. Using patient-matched samples of normal breast tissue and breast cancer by mass spectrometry we revealed elevated levels of NUCKS in protein extracts from ductal breast cancers [11].…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations